A safety evaluation of guselkumab for the treatment of psoriasis. Issue 7 (3rd July 2018) - Galluzzo, M.; D'Adamio, S.; Campione, E.; Bianchi, L.; Talamonti, M.
ABSTRACT: Introduction : Guselkumab is a fully human monoclonal IgG1λ antibody for the treatment of plaque psoriasis that inhibits interleukin (IL)-23p19 subunit, reducing the proliferation of type 17 helper T (Th-17) cells and thus production of Th-17-derived pro-inflammatory cytokines, especially IL-17 and IL-22. Areas covered : In the following article, the mechanism of action and mainly the efficacy and safety profile of guselkumab available from results of trials will be discussed. We summarized these data after a literature review including PubMed search, relating proceedings and abstracts from relevant international conferences, assessment reports from European and United States regulatory agencies and treatment guidelines up to April 2018. Expert opinion : The central role of IL-23 in psoriasis pathogenesis is supported by genetic links of IL-23 and IL-23R alleles to psoriasis susceptibility; early clinical trials have demonstrated that sufficient inhibition of IL-23p19 results in rapid resolution of the disease. Targeting IL-23, may be responsible for the high efficacy and durable responses of guselkumab, avoiding some adverse effects of IL-17A blockade, like mucocutaneous candida infections or triggering/worsening of inflammatory bowel disease, experienced with agents acting selectively against this molecule and that seem to be class related.